MENINGKATKAN KEMAMPUAN BERBICARA PADA ANAK USIA 5-6 TAHUN MELALUI METODE BERMAIN PERAN DI PAUD PELANGI KASIH KECAMATAN TENAYAN RAYA KOTA PEKANBARU - Hutabarat, Renofa; Jas, Jaspar; Chairilsyah, Daviq (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract :This study aimed to investigate the effect on the ability of activities Role Playing Talking Children. The study consists of two variables: Speech and Role Playing The hypothesis proposed in this study are as follows: Through the implementation of role-playing activities can improve speaking skills of children aged 5-6 years in early childhood Pekanbaru Pelangi Kasih ". The results showed no significant positive correlation between the activities bermian Role with the ability to speak. The ability to speak the child always has increased in each cycle.From the observation of an increase in the ability to speak on the analysis of data where the average acquisition value ranging from pre-cycle to the first cycle is 31% with the criteria began to develop, the first cycle to the second cycle began to develop criteria 47.9%, from the average value from pre-cycle to the second cycle of 96% with the criteria developed very well. Increased ability to talk children through role-playing activities has increased significantly with the acquisition of the end of the second cycle by 96%, then the study is considered successfulKeywords : Speech, Role Playing